Da aplicação do conceito de pessoa com deficiência para o fim de proteção por meio do benefício assistencial de prestação continuada - Oliveira, Nayara Maria Silvério da Costa Dallefi (2020)
This paper aims to examine the role and evolution of jurisprudence in the conceptual delimitation of dissability for the purpose of granting the benefit of continued benefit. To this end, it was first necessary to addres the protection of persons with disabilities from the aerliest days of society and its evolution to the presente day, especially after the New York Convention that which specifically adresses the issue in 2007. This is because, this Convention was crucial point for the insertion of the matter in the nacional law, with reflexes in several braches of the material law and, especially in the analysis oh the concepto f person with disabilities, for the purposes of granting the benefit of continuous provision. In spite of the concept os disabled person in the light of the Disabled Person Statute, Law nº 13.146/2015, it was up to the Judiciary to interpret, on a case-by-case basis, the situations for granting the benefit of continued provision for the person with a disability, positioning itself about the limits, the reach and the scope of this concept. This time, the presente study, from a historical-legal reserach, intends to analyze, the domestic jurisprudence considering the decisions handed down within the socipe of the Regional Federal Courts ans Superior Courts in order to identify elements that allow to detect whether or not there is na effective line and concrete uniformity in the construction of the concepto f person with disabilites for the purpose of granting the benefit of continued provision, in the light of the current legislation, in view of greater legal security. Thus, using the inductive method and, in na specific criteria to be considered in the judgment of cases brought to the Judiciary to obtain the benefit of continued provision for the person with disabilities, in order to establish and put in place a jurisprudence based on a construction of the concepto f disability that enables the implementation of the principles of equality and legal certainty for the protected community